Radon‐traced pore‐water as a potential source of CO2 and CH4 to receding black and clear water environments in the Amazon Basin. Issue 5 (7th August 2018) - Call, Mitchell; Sanders, Christian J.; Enrich‐Prast, Alex; Sanders, Luciana; Marotta, Humberto; Santos, Isaac R.; Maher, Damien T.
Abstract: Groundwater is a primary source of dissolved CO2 and CH4 in Amazonian headwaters, yet in higher order rivers, a groundwater/pore‐water source is difficult to constrain due to the high spatial and temporal heterogeneity of pore‐water exchange. Here, we report coupled, high resolution measurements of p CO2, CH4, and 222 Rn (a natural pore‐water and groundwater tracer) during receding waters in the three major water types of the Central Amazon Basin: black (Negro River); clear (Tapajós River); white (Madeira River). Considerable spatial heterogeneity was observed in p CO2, CH4, and 222 Rn concentrations ranging from 460 μatm to 8030 μatm, 7 nM to 281 nM, and 713 dpm m −3 to 8516 dpm m −3, respectively. The significant correlations between p CO2 and CH4 to 222 Rn in the black and clear waters suggests that pore‐water further enhanced CO2 supersaturation by 18–47% and is a driver of CH4 dynamics in these waters.